Primary Non-Hodgkin's Lymphoma of Stomach: To Report 54 Patients and Analysis of Major Reported Series. (23rd October 2013) - Ansari, Mansour; Nasrolahi, Hamid; Kani, Amir Abbas; Hamedi, Seyed Hasan; Razzaghi, Samira; Ahmadloo, Niloofar; Mohammadianpanah, Mohammad; Omidvari, Shahpour; Mosalaei, Ahmad
Abstract : Introduction . This study aimed to report the characteristics, prognostic factors, and treatment outcomes of 54 patients with primary gastric lymphoma. Materials and Methods . This retrospective study was carried out by reviewing the medical records of 54 adult patients diagnosed at a tertiary academic hospital. All the patients were treated with curative intent. Forty-four patients (81.5%) underwent gastrectomy followed by adjuvant chemotherapy and/or radiotherapy, whereas 10 ones (18.5%) were treated with chemotherapy alone or with radiotherapy. Results . The study was conducted on 25 males and 29 females with the median age of 50 years. Diffuse large B-cell lymphoma (DLCL) (67%) and Mucosa Associated Lymphoid Tissue (MALT) lymphoma (26%) were the most common histologic types. Besides, 36 (59%), 16 (30%), 5 (9%), and 1 (2%) patients were in stages I, II, III, and IV, respectively. The 5-year disease-free survival and overall survival were 64.7% and 67%, respectively. In univariate analysis for overall survival, International Prognostic Index (IPI) (P < 0.001 ), the WHO performance status (P < 0.001 ), Ann Arbor stage (P = 0.027 ), age (P = 0.034 ), and LDH serum level (P < 0.001 ) were the prognostic factors. Conclusion . Gastric lymphoma tends to present in early stage of the disease and has a favorable outcome.